Hadith Education in Forming Character of Early Childhood - Muhammad Hambal (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Early childhood is a very brilliant time in the process of character formation, because early age is a time where children absorb a lot of knowledge to be applied in the future. We see the character of the nation's children in this era, the term